Peran Aktor Kebijakan Pembatasan Sosial Berskala Besar Dalam Mengatasi Penyebaran COVID-19 Di Indonesia - Diki Suherman (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2020)
Indonesia is one of the countries affected by COVID-19 (corona virus), Local Distance and Rafid Test (Mass Test) as a step to overcome corona so that it does not spread widely. However, the fact is that positive cases in Indonesia occurred at the beginning of March which increased, on April 5, 2020, positive cases of COVID-19 in Indonesia reached 2,273 cases, 198 died and 164 recovered. The Indonesian government issued a new policy in dealing with the spread of COVID-19 (corona) through the Large-Scale Social Restriction Policy (PSBB) as an effort to break the chain of the spread of this virus which was stipulated in Government Regulation No.21 of 2020 concerning Large-Scale Social Restrictions in the Context of Accelerated Handling of Corona Virus Disease 2019 (COVID-19). The purpose of this journal is to describe the role of large-scale social restrictions (PSBB) policy actors in overcoming the spread of COVID-19 (corona). The method used is qualitative by collecting data using library research sourced from journals, regulations and articles related to policy actors in overcoming COVID-19 (corona) and accountable information media. The results of this journal show that the large role of actors involved in the Large-Scale Social Clearance (PSBB) policy in breaking the chain of the spread of COVID-19 (corona) in Indonesia, this policy can work well when collaboration is built with 5 (five elements) subject or stakeholder elements , namely: Academicians (Academics), Business (Entrepreneurs), Community (society), Government (government) and Media (Mass Media).